Connexin32 deficiency exacerbates carbon tetrachloride-induced hepatocellular injury and liver fibrosis in mice. (12th June 2016) - Cogliati, Bruno; Crespo Yanguas, Sara; Da Silva, Tereza Cristina; Aloia, Thiago Pinheiro Arrais; Nogueira, Marina Sayuri; Real-Lima, Mirela Aline; Chaible, Lucas Martins; Sanches, Daniel Soares; Willebrords, Joost; Maes, Michaël; Pereira, Isabel Veloso Alves; Castro, Inar Alves de; et al.
Abstract: Objective: Liver fibrosis results from the perpetuation of the normal wound healing response to several types of injury. Despite the wealth of knowledge regarding the involvement of intracellular and extracellular signaling pathways in liver fibrogenesis, information about the role of intercellular communication mediated by gap junctions is scarce. Methods: In this study, liver fibrosis was chemically induced by carbon tetrachloride in mice lacking connexin32, the major liver gap junction constituent. The manifestation of liver fibrosis was evaluated based on a series of read-outs, including collagen morphometric and mRNA analysis, oxidative stress, apoptotic, proliferative and inflammatory markers. Results: More pronounced liver damage and enhanced collagen deposition were observed in connexin32 knockout mice compared to wild-type animals in experimentally triggered induced liver fibrosis. No differences between both groups were noticed in apoptotic signaling nor in inflammation markers. However, connexin32 deficient mice displayed decreased catalase activity and increased malondialdehyde levels. Conclusion: These findings could suggest that connexin32-based signaling mediates tissue resistance against liver damage by the modulation of the antioxidant capacity. In turn, this could point to a role for connexin32 signaling as a therapeutic target in the treatment of liver fibrosis.